KONTRIBUSI KETERAMPILAN MEMBACA KRITIS TERHADAP KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS VIII SMP NEGERI 1 MAPAT TUNGGUL SELATAN - Fitri, Rahmi Laila; Basri, Irfani (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT The purpose of this study is as follows. First, describe the critical reading skills of students of class VIII SMP Negeri 1 Mapat Tunggul Selatan. Second, it describes the writing skills text exposition of grade VIII SMP Negeri 1 Mapat Tunggul Selatan. Thirdly, analysing the contribution of the reading skills of critical writing skills text exposition of grade VIII SMP Negeri 1 Mapat Tunggul Selatan. Type of this research is a descriptive method quantitative research. The design of research i.e. research korelasional. This research population is grade VIII SMP Negeri 1 Mapat Tunggul Selatan 2018/2019 school year with a total of 50 people scattered in two classes. A sample of these studies amounted to 50 people. Sampling techniques in the study are the total sampling. Variables this research is critical reading skills as free variables (X) and writing skills text exposition as a variable (Y). The instruments used in this research is an objective test for critical reading skills and test performance for writing skills text Exposition. The results of the research there are three, as follows. First, critical reading skills of students of class VIII SMP Negeri 1 Mapat Tunggul Selatan qualified enough, with an average value of 57.08 is under the KKM (75). Second, the skills of writing a text exposition of grade VIII SMP Negeri 1 Mapat Tunggul Selatan qualified enough, with an average value of 59.67 is under the KKM (75). Third, there is a positive and significant contribution between critical reading skills with writing skills text exposition of grade VIII SMP Negeri 1 Mapat Tunggul Selatan at significant level 95% and the degrees of freedom (dk) = n-1 because thitung > ttabel IE 3.03 > 1.68. Based on the results of this study it was concluded that there is a linear relationship between critical reading skills with writing skills text exposition of grade VIII SMP Negeri 1 Mapat Tunggul Selatan with a confidence level of 95%. In other words, if the student's critical reading skills are good, then the exposition text writing skills students are also good. In contrast, when bad Exposition text skills, then writing skills students also bad Exposition text. Kata Kunci: Kontribusi, Membaca Kritis, Menulis Teks Eksposisi